Developing English Textbook for Pre-Service Flight Attendant Students - Muhamad Ali Agung Baroto; Emalia Iragiliati; Mirjam Anugerahwati (Universitas Negeri Malang, 2017)
Abstract: This study is intended to develop a textbook for pre-service flight attendant students having training in the flight attendant training center. The developed textbook is based on the existing syllabus and need analysis period. The developmental research from Borg and Gall is implemented. The needs survey is implemented to pre-service students, ESP teachers in Sekar Gegani, and experienced flight attendants. The developed product contains ten units related to actual working atmosphere in-flight. They are: 1) Pre-flight briefing 2) Boarding, 3) Announcement 4) Before Take-off, 5) Meal Service, 6) Dealing with problem, 7) Sales on board, 8) Emergency, 9) Disembarking, and 10) Getting a job. Key Words: Textbook, ESP, Pre-service flight attendants Abstrak: Penelitian ini bertujuan untuk mengembangkan buku untuk calon pramugari yang sedang menempuh pendidikan di lembaga pendidikan dan pelatihan. Buku dikembangkan berdasarkan syllabus yang ada dan temuan pada fase need analisis. Penelitian pengembangan berdasarkan teori Borg and Gall. Survey untuk mendapatkan data di lakukan pada calon pramugari,instruktur, dan pramugari berpengalaman. Buku terdiri dari 10 unit meliputi 1) Briefing sebelum terbang 2) Boarding, 3) pengumuman 4) Before Take-off, 5) Meal Service, 6) Dealing with problem, 7) Sales on board, 8) Emergency, 9) Disembarking, and 10) Getting a job Kata kunci: Buku, bahasa inggris penerbangan, calon pramugari